2016
DOI: 10.1080/17474124.2016.1242410
|View full text |Cite
|
Sign up to set email alerts
|

Bone status assessed by quantitative ultrasound in children with inflammatory bowel disease: a comparison with DXA

Abstract: Low bone mineral density often complicates IBD in children. QUS is not an appropriate method for the assessment of bone status in children. Nutritional status seems to have a greater impact on bone status than corticosteroids therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Nutritional status seems to have a greater impact on bone status than corticosteroid therapy (425). Children with IBD are at particularly risk for vitamin D deficiency, but this was not found to be directly associated with osteopenia (426).…”
Section: Nutrition Growth and Bone Healthmentioning
confidence: 93%
“…Nutritional status seems to have a greater impact on bone status than corticosteroid therapy (425). Children with IBD are at particularly risk for vitamin D deficiency, but this was not found to be directly associated with osteopenia (426).…”
Section: Nutrition Growth and Bone Healthmentioning
confidence: 93%
“…The results are inconsistent and difficult to compare to our study, partly because a number of studies investigated different populations or used different measurement sites of QUS. Seven studies used the same equipment as we did, comparing pQUS to DXA ( Di Mase et al, 2012 ; Gonçalves et al, 2014 ; Pluskiewicz et al, 2002 ; Bąk-Drabik et al, 2016 ; Catalano et al, 2017 ; Halaba et al, 2005 ; Catalano et al, 2013 ). The correlation coefficients between pQUS and DXA found by Pluskiewicz et al (2002) and Di Mase et al (2012) are in agreement with our calculations (0.45–0.56 and 0.42–0,52, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the association between the measurements of DXA and QUS revealed inconsistent results. While a number of studies showed a significant positive correlation between DXA and QUS ( Van Rijn et al, 2000 ; Di Mase et al, 2012 ; Falcini et al, 2000 ; Gonçalves et al, 2014 ; Hartman et al, 2004a ; Pluskiewicz et al, 2002 ; Sani et al, 2011 ; Sundberg et al, 1998 ; Xu et al, 2014 ; Bąk-Drabik et al, 2016 ; Catalano et al, 2017 ; Olszynski et al, 2016 ; Zuckerman-Levin et al, 2007 ; Mora et al, 2009 ; Weeks et al, 2016 ; Halaba et al, 2005 ; Catalano et al, 2013 ), others found a discrepancy between the measurements of the two methods ( Gianni et al, 2008 ; Halaba et al, 2005 ; Chong et al, 2015 ; Christoforidis et al, 2010 ; Christoforidis et al, 2011 ; Hartman et al, 2004b ; Williams et al, 2012 ; Alwis et al, 2010 ). This could be a result of the different QUS measurement sites or different patient categories investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many examples of clinical DXA applications in pediatric cohorts to reveal disturbances of bone metabolism, e.g., in girls with anorexia nervosa [16], children with end-stage renal disease [68], or patients with inflammatory bowel disease [17]. The clinical values of DXA measurements are somewhat limited by their very nature, namely that the results (bone mineral density—BMD) are estimated from a single trait—calcium content in bone tissue, while not reflecting possible architectural changes in bone structure (qualitative characteristics) [15].…”
Section: Introductionmentioning
confidence: 99%